THE VIBRATION REDUCTION OF CONTINUOUS MOVING LOADS ON A NONLINEAR SIMPLE BEAM RESTING ON AN ELASTIC FOUNDATION - Wang, Yi-Ren; Hung, Chien-Chun; Huang, Hsin (Journal of Applied Engineering Science, 2021)
This technical note investigates a hinged-hinged nonlinear Euler-Bernoulli beam resting on an elastic foundation subjects to moving loads. The method of multiple scales (MOMS) is employed to analyze this nonlinear beam model. The fixed points plots are made to identify the system’s internal resonance. The frequency ratio plot is proposed to predict the system internal resonance conditions. This study improved the author’s earlier work for a wider range of prediction on internal resonance conditions. The continuous concentrated moving loads are applied to this nonlinear beam model. The dynamic vibration absorber (DVA) is attached on the beam to reduce vibration and prevent internal resonance. The mass, spring constant and location of the DVA are studied to obtain the best damping effect on the nonlinear beam with moving loads. The results are verified by numerical results and ANSYS simulations.
Keywords: internal resonance, fixed points plot, vibration, dynamic vibration absorber